1971
DOI: 10.1063/1.1660552
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Kinetics of Plastic Deformation

Abstract: An argument is presented in which it is shown that the deformation process in a crystal is identical with the isomerization of a giant molecule and that the study of plastic flow is part of chemical kinetics. This view leads to a general expression for the rate constant which describes the kinetics of the thermally activated dislocation movement associated with a system of consecutive and parallel energy barriers. The application of the kinetic equation is illustrated with several specific examples.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

1972
1972
2011
2011

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(7 citation statements)
references
References 5 publications
0
7
0
Order By: Relevance
“…Using chemical kinetics and deformation kinetics concepts [5] the theory of consecutive bond breaking processes associated with steady state plastic flow was formulated by Krausz and Eyring [6]. Using chemical kinetics and deformation kinetics concepts [5] the theory of consecutive bond breaking processes associated with steady state plastic flow was formulated by Krausz and Eyring [6].…”
Section: Discussionmentioning
confidence: 99%
“…Using chemical kinetics and deformation kinetics concepts [5] the theory of consecutive bond breaking processes associated with steady state plastic flow was formulated by Krausz and Eyring [6]. Using chemical kinetics and deformation kinetics concepts [5] the theory of consecutive bond breaking processes associated with steady state plastic flow was formulated by Krausz and Eyring [6].…”
Section: Discussionmentioning
confidence: 99%
“…Following the theory of absolute reaction rates, Becker [21] first supposed and showed that thermal fluctuations can promote slip in crystals and, at high temperatures, decrease shear stresses necessary for slip. Startsev et al [22], Krausz and Eyring [23] have confirmed that one can consider an elementary act of plastic deformation, displacement of a dislocation, in a crystal as an atomic rearrangement in a peculiar gigantic molecule. In fact, this process is equivalent to a special chemical reaction.…”
Section: Determination Of the Critical Temperaturementioning
confidence: 85%
“…where AF is the change of the Gibbs free energy of activation (thermodynamic potential), A U is the activation enthalpy (energy), AS is the entropy change, iz~l is a structure factor, which, according to Gibbs [23], involves the density of movable dislocations and geometric characteristics, and exp (AS~r) is the entropy term, appearing in the equations including the activation enthalpy (energy) U and a preexponential multiplier E~l. Equation (3) is considered valid for the rate of plastic deformation under constant stress ( ~ = const) at the prescribed stage of creep and active deformation.…”
Section: Determination Of the Critical Temperaturementioning
confidence: 99%
See 1 more Smart Citation
“…Based on the Arrhenius-equation, Krausz and Eyring [58] described the plastic deformation using the kinetics of chemical reactions, ̇ , where ̇ is the strain rate during plastic deformation, is Burgers vector in terms the magnitude of dislocation movement of atoms, is dislocation density and is dislocation velocity. According to this description, they derived a temperature-dependent rate constant, , to describe the strain rate in a plastic deformation area:…”
Section: The Arrhenius-type Equation and Rate Controlling Theorymentioning
confidence: 99%